PENGARUH AUDITOR RELATIONSHIPS TERHADAP KUALITAS AUDIT PADA PERUSAHAAN MANUFAKTUR DI INDONESIA (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar pada Bursa Efek Indonesia Tahun 2011) - Wisanggeni, Antonius Anadri; Ghozali, Imam (Diponegoro Journal of Accounting, 2017)
The objective of this study is to provide empirical evidence on the association of audit quality with audit tenure which would support the argument for auditor rotation being prescribed by regulation in Indonesia. Audit tenure is measured having regard to both the duration of relations between the lead audit partner and client firm management (person to person relations), as well as the duration of the audit firm’s engagement by the client (firm to firm). Using the setting of when Indonesia firm were adopting the International Financial Reporting Standards (IFRS). We examine 79 publicly listed Indonesia firms period of 2011. By using regression analysis technique, the results show that evidence of a negative association between the length of tenure between the lead audit partner and client firm management (person-to-person relations) and audit quality. Conversely we find a negative relation between audit firm engagement by the client (firm-to-firm) and audit quality.